Training of Caregivers of Ischemic Stroke Patients in Neurology ward: An Assessor Blind Randomized Controlled Trial (Bangladesh Journal of Neuroscience, 2026)
Background: Management of stroke patients in low resource settings like Bangladesh largely depends upon their caregivers who are mostly unskilled family members. The effect of a structured caregiver-training program on stroke patients has not been studied adequately in Bangladesh. This study was conducted to evaluate the effect of caregivers’ training in improving outcome of stroke patients.Methods and Materials: This assessor blind randomized controlled trial was performed in the Department of Neurology, Chittagong Medical College Hospital, Chattogram for a period of two years. One hundred and fortynine stroke patients and their care givers were randomly divided into two groups: the intervention arm and the control arm. Caregivers in the intervention arm received actively two sessions of training according to modified London Stroke Carers Training Course manual before their patients are discharged from the hospital. The functional status of patients from both groups was evaluated by the Barthel Index score (BI) and Modified Rankin scale (MRS) score at base line and at two, four and six months.Results: Baseline characteristics and functional status of patients and caregivers of both arms were similar (p=>0.05). Median value of interval from stroke onset to hospitalization was 1 and 0 days in the intervention and control arm, respectively (p=0.897) and median length of stay in hospital was 5 days in both arms (p=0.360). Patients in the intervention arm had significant improvement in their median BI from baseline to 6 months (10 and 100; p=